Charmaine Solomon: The Complete Asian Cookbook - Davidson, Alan (Petits Propos Culinaires, 2024)
Charmaine Solomon: The Complete Asian Cookbook: Grub Street, London, 2002: ISBN 1904010180: 512 pp., colour photos, h/b, £25.00.